1991
DOI: 10.1101/gad.5.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Germ-line intrachromosomal recombination restores fertility in transgenic MyK-103 male mice.

Abstract: Males of the MyK-103 line of transgenic mice are fertile and sire litters of normal size, but they never transmit the transgene, whereas females transmit the transgene with normal frequency. The chromosome originally bearing the transgene can be transmitted through the male germ line, but only after the transgene is deleted or rearranged by intrachromosomal recombination. The transgene encodes a functional herpes simplex virus (HSV) thymidine kinase gene that causes sperm infertility when expressed in postmeio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Mitotic (54). Our analysis of the OPP line, in which a prescreening of whole seminiferous tubules was performed, was consistent with jackpot events in germ line precursors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Mitotic (54). Our analysis of the OPP line, in which a prescreening of whole seminiferous tubules was performed, was consistent with jackpot events in germ line precursors.…”
Section: Discussionsupporting
confidence: 76%
“…In those experiments, nearly all of the sperm in a hemizygous male stained positive for human growth hormone. Additional histological and functional evidence for this process has been obtained in studies of the Myk-103 transgenic mice (54) and mice hemizygous for an mPl locus (10). If the lacZ gene product were to behave similarly in our system, we would expect that a single correction event would result in multiple blue cells, depending on the number of cells connected in a syncytium (about 128 [19]) and the distance to which diffusion would detectably occur.…”
Section: Resultsmentioning
confidence: 71%
“…In studies of random murine transfection integrants, the majority of stable insertions were H/T, and recombination prior to integration was suggested as an explanation for this nonrandom distribution (15). However, in swine transgenic constructs (20) and several murine transgenic constructs (66,67), complex integrants were found to be present primarily as H/H or T/T insertions. Perhaps the distribution of H/H and T/T insertions in mammalian cells suggests that, as in bacteria (30), inverted repeat structures are unstable and the cellular machinery provides strong negative selection against such insertions when introducing naked DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, Southern blot analysis with a neo probe indicated that of 60 Agouti offspring none carried the transgene. It is possible that the transgene inactivates a gene that is imprinted or essential in haploid sperm cells; alternatively, the transgene may be unstable in the germ line (Wilkie et al 1991). In the ROSA~-geo25 strain, heterozygous animals were consistently 25-40% smaller than their wild-type littermates.…”
Section: Phenotypes Associated With Promoter Trap Eventsmentioning
confidence: 99%